Austenitic stainless steel

By controlling the presence state of hydrogen and using the temperature-raising dehydrogenation analysis method, combined with heat treatment and the formation of fine compounds, the problem of the existing austenite stainless steel need to add expensive alloy elements when improving hydrogen embrittlement resistance, and achieving high hydrogen embrittlement resistance and low-cost austenite stainless steel.

CN119768549APending Publication Date: 2025-04-04NIPPON STEEL STAINLESS STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380061119.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-24
Filing Date
2023-08-08
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When existing austenitic stainless steels improve hydrogen embrittlement resistance, they need to add expensive alloy elements, which increases the cost of alloy.

Method used

By controlling the presence state of hydrogen, it is difficult for hydrogen to move inside the steel. The hydrogen release amount, peak temperature and peak velocity are measured by heating dehydrogenation analysis method, and hydrogen is captured and stabilized through heat treatment and the formation of fine compounds to avoid its aggregation and movement.

Benefits of technology

It realizes an austenitic stainless steel with excellent hydrogen embrittlement resistance without the use of expensive alloy elements, reducing alloy cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768549A_ABST
    Figure CN119768549A_ABST
Patent Text Reader

Abstract

An austenitic stainless steel having a hydrogen release amount [H] of less than 10.0 ppm, a hydrogen release peak temperature [Tp] of 350 DEG C or more, a hydrogen release peak velocity [Rmax] of 0.050 ppm / min or less, and a hydrogen release peak temperature [Tp] of 350 DEG C or more and a hydrogen release peak velocity [Rmax] of 0.050 ppm / min or less when the amount of hydrogen released in the temperature range of 25-800 DEG C is measured using a temperature rise dehydrogenation analysis method at a temperature rise rate of 100 DEG C / h. The austenitic stainless steel has a number density of compounds having a diameter of 0.1-2 [mu] m of 1.0-10.0 particles / mm2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to austenitic stainless steel. Background Art

[0002] In recent years, hydrogen has attracted attention as a new energy source to replace fossil fuels. Hydrogen is a clean energy source that does not emit carbon dioxide. On the other hand, hydrogen, for example, can cause hydrogen embrittlement, thereby embrittlement of raw materials. Therefore, Patent Document 1 discloses an austenitic stainless steel with improved hydrogen embrittlement resistance.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-196842 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] However, in order to improve the hydrogen embrittlement resistance, many expensive alloying elements are added to the austenitic stainless steel disclosed in Patent Document 1, which increases the alloy cost. Therefore, it is a difficult technical problem to improve the hydrogen embrittlement resistance in austenitic stainless steel without using expensive alloying elements as essential elements.

[0008] In view of the above circumstances, an object of the present invention is to solve the above-mentioned technical problems and to provide an austenitic stainless steel having excellent hydrogen embrittlement resistance without using expensive alloy elements as essential elements.

[0009] Solutions for solving problems

[0010] The present invention has been made to solve the above-mentioned technical problems, and the gist of the present invention lies in the following austenitic stainless steel.

[0011] (1) An austenitic stainless steel, wherein when the amount of hydrogen released in a temperature range of 25 to 800° C. is measured at a heating rate of 100° C. / h using a temperature dehydrogenation analysis method,

[0012] The amount of hydrogen released [H] is less than 10.0ppm,

[0013] The peak temperature [Tp] of hydrogen release is above 350°C.

[0014] The peak rate [Rmax] of hydrogen release is 0.050 ppm / min or less.

[0015] The number density of the compound with a diameter of 0.1 to 2 μm in the austenitic stainless steel is 1.0 to 10.0 per mm 2 .

[0016] (2) The austenitic stainless steel according to (1) above, wherein the chemical composition of the austenitic stainless steel is:

[0017] C: 0.080% or less,

[0018] Si: 1.00% or less,

[0019] Mn: 2.00% or less,

[0020] P: 0.050% or less,

[0021] S: 0.020% or less,

[0022] Cr: 17.0~22.0%,

[0023] Ni: 8.0-13.0%,

[0024] N: 0.250% or less,

[0025] Nb: 0~0.20%,

[0026] Ti: 0~0.20%,

[0027] Mo: 0-1.0%,

[0028] Cu: 0-1.0%,

[0029] Al: 0-0.30%,

[0030] Co: 0-0.50%,

[0031] V: 0~0.50%,

[0032] W: 0~0.50%,

[0033] B: 0~0.0050%,

[0034] Ca: 0~0.010%

[0035] Mg: 0~0.010%,

[0036] Zr: 0~0.50%,

[0037] Ga: 0~0.05%,

[0038] Hf: 0~0.10%,

[0039] REM: 0~0.10%,

[0040] Balance: Fe and impurities.

[0041] (3) The austenitic stainless steel according to (1) or (2) above, which is used in a high-pressure hydrogen environment or a liquefied hydrogen environment.

[0042] (4) The austenitic stainless steel according to (1) or (2) above, which is used for a component of a hydrogen production device or a hydrogen supply device.

[0043] Effects of the Invention

[0044] According to the present invention, an austenitic stainless steel having excellent hydrogen embrittlement resistance can be obtained without using expensive alloy elements as essential elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a schematic diagram showing a hydrogen release curve (TDA curve). DETAILED DESCRIPTION

[0046] The present inventors conducted various studies to improve the hydrogen embrittlement resistance of austenitic stainless steel and simplify the alloy, and obtained the following findings (a) to (c).

[0047] (a) Austenitic stainless steel is prone to hydrogen embrittlement in a hydrogen environment of -100 to -40°C. This is believed to be because within this temperature range, the austenite phase (hereinafter also referred to as the "γ phase") becomes unstable, and strain accumulation and the like cause the phase transformation to the fragile α' phase. Therefore, in order to improve the stability of the γ phase, it is possible to consider increasing the content of added elements such as Ni, Cu, and Mn. On the other hand, when the content of the above elements is increased to form a high alloy, the cost of the alloy increases.

[0048] (b) Therefore, the inventors of the present invention have focused on the hydrogen contained in the steel in order to improve the hydrogen embrittlement resistance without forming a high alloy. In the usual steel manufacturing process and hydrogen environment, hydrogen will invade the steel, so that a small amount of hydrogen is absorbed into the steel. For example, when the hydrogen in such steel is accumulated in the part where the strain is accumulated, hydrogen embrittlement is promoted. Therefore, although it is preferred to release the hydrogen in the steel, it is difficult to release the hydrogen to the outside of the steel when hydrogen exists in the low temperature use environment.

[0049] (c) Therefore, it is desirable to suppress the aggregation of hydrogen existing inside the steel and make it difficult for hydrogen to move. That is, it is effective to control the state of existence of hydrogen in a manner that hydrogen is captured inside the steel. In terms of controlling the state of existence of hydrogen, it is preferred to perform a long-term heat treatment at a temperature range of 50 to 400°C during manufacturing. In addition, it is also effective to pre-form sufficient fine compounds containing Ti and Nb that help capture hydrogen.

[0050] One embodiment of the present invention has been accomplished based on the above findings. Hereinafter, various conditions of the austenitic stainless steel according to the present embodiment will be described in detail.

[0051] 1. Existence of Hydrogen

[0052] In the austenitic stainless steel of the present embodiment, the state of hydrogen is controlled so that hydrogen is difficult to move inside the steel, that is, hydrogen is captured. In order to quantitatively grasp the state of hydrogen, a temperature dehydrogenation analysis method is used for the austenitic stainless steel of the present embodiment.

[0053] Temperature Dehydrogenation Analysis is a method of heating stainless steel at a constant heating rate and detecting the released hydrogen using a gas chromatograph or a quadrupole mass spectrometer. Hydrogen is captured by many defects such as atomic vacancies, dislocations, lattice defects such as grain boundaries, precipitates, and inclusion interfaces. And, by using the Temperature Dehydrogenation Analysis, the amount of hydrogen captured by these defects can be quantitatively evaluated.

[0054] Here, refer to Figure 1 The hydrogen release curve obtained by the temperature dehydrogenation analysis method (hereinafter also referred to as the "TDA curve") is explained. In the TDA curve, the horizontal axis is the temperature and the vertical axis is the hydrogen release rate. Generally speaking, the TDA curve of steel is a curve in which the hydrogen release rate reaches a peak at a certain temperature. In addition, in the TDA curve, the temperature at which the hydrogen release rate reaches a peak is called the peak temperature of hydrogen release [Tp]. In addition, the hydrogen release rate at this time is called the peak rate of hydrogen release [Rmax]. In addition, by integrating the curve, the amount of released hydrogen [H] can also be calculated.

[0055] The amount of released hydrogen [H], the peak temperature of hydrogen release [Tp], and the peak rate of hydrogen release [Rmax] are respectively used as indices showing the state of existence of hydrogen in steel.

[0056] Furthermore, when the amount of hydrogen released in the temperature range of 25 to 800°C was measured using a temperature rise dehydrogenation analysis method at a temperature rise rate of 100°C / h, the amount of released hydrogen [H] was less than 10.0 ppm, the peak temperature [Tp] of hydrogen release was above 350°C, and the peak rate of hydrogen release [Rmax] was below 0.050 ppm / minute.

[0057] When the amount of released hydrogen [H] measured by the above method is 10.0 ppm or more, excessive hydrogen will be absorbed in the steel, and it is difficult to improve the hydrogen embrittlement resistance. Therefore, the amount of released hydrogen [H] is less than 10.0 ppm. The amount of released hydrogen [H] is preferably 8.5 ppm or less, and more preferably 6.5 ppm or less. It should be noted that in the austenitic stainless steel of the present embodiment, since the hydrogen that cannot be released is captured, the amount of released hydrogen [H] is preferably more than 1.0 ppm, and more preferably 1.5 ppm or more.

[0058] In addition, when the peak temperature [Tp] of hydrogen release is less than 350°C, the degree of hydrogen capture is low and hydrogen easily moves in the steel. Therefore, the peak temperature [Tp] of hydrogen release is 350°C or higher. The peak temperature [Tp] of hydrogen release is preferably 370°C or higher, and more preferably 400°C or higher. It should be noted that the upper limit of the peak temperature [Tp] of hydrogen release is not particularly limited, but is, for example, 500°C or higher.

[0059] In addition, when the peak rate [Rmax] of hydrogen release exceeds 0.050ppm / min, the degree of hydrogen capture is low and hydrogen becomes easy to move in the steel. Therefore, the peak rate [Rmax] of hydrogen release is 0.050ppm / min or less. The peak rate [Rmax] is preferably 0.045ppm / min or less, and more preferably 0.035ppm / min or less. It should be noted that the lower limit of the peak rate [Rmax] of hydrogen release is not particularly limited, but is, for example, 0.005ppm / min or more.

[0060] It should be noted that the amount of released hydrogen [H], the peak temperature of hydrogen release [Tp], and the peak rate of hydrogen release [Rmax] are measured by the temperature rise dehydrogenation analysis method. Specifically, the measurement can be carried out according to the following steps.

[0061] After cutting a test piece of 10 mm (width direction) × 30 mm (rolling direction) from the steel plate, degrease and clean the test piece with an organic solvent. Next, use the test piece to evaluate by measuring the desorbed hydrogen using temperature dehydrogenation analysis (TDA). In TDA, the test piece is heated in an argon atmosphere at a heating rate of 100°C / h in a temperature range of 25°C (room temperature) to 800°C, and the hydrogen released (desorbed) from the test piece is measured by a chromatograph. The chromatograph used is capable of detecting hydrogen with an accuracy of 0.01 ppm. Based on the measurement results of TDA, the following is made: Figure 1 The TDA curve shown is used to calculate the amount of released hydrogen [H], the peak temperature of hydrogen release [Tp], and the peak rate of hydrogen release [Rmax]. It should be noted that the amount of released hydrogen can be calculated by integrating the curve.

[0062] 2. Number density of compounds

[0063] Furthermore, in order to achieve a state where hydrogen is firmly captured in the steel, the number density of the compounds is controlled in the austenitic stainless steel of the present embodiment. Specifically, the number density of compounds with a diameter of 0.1 to 2 μm is 1.0 to 10.0 pcs / mm. 2 .

[0064] Fine precipitates containing Nb and / or Ti, specifically carbides and carbonitrides, have a diameter of 0.1 to 2 μm and are effective in capturing hydrogen. Therefore, the number density of compounds with a diameter of 0.1 to 2 μm is 1.0 precipitate / mm 2 This is because the number density of compounds with a diameter of 0.1 to 2 μm is less than 1.0 / mm 2 The number density of compounds with a diameter of 0.1 to 2 μm is preferably 1.5 / mm 2 above.

[0065] On the other hand, the number density of compounds with a diameter of 0.1 to 2 μm is 10.0 / mm 2 This is because the number density of compounds with a diameter of 0.1 to 2 μm exceeds 10.0 / mm 2 When the diameter of the compound is 0.1 to 2 μm, the number density is preferably 8.5 / mm. 2 Below, more preferably 6.5 pieces / mm 2 the following.

[0066] The number density of the compound can be measured by the following steps. Prepare the measurement sample according to JIS Z 0555:2003. Prepare a measurement area of ​​72mm 2 For the measurement sample, use the inclusion automatic analyzer attached to the SEM to confirm the compounds with a diameter of 0.1 to 2 μm, and measure their number density. Here, the above diameter refers to the circle equivalent diameter, which can be calculated by the inclusion automatic analyzer. In addition, as an inclusion automatic analyzer, for example, MQA (Metal Qiality Analyzer: registered trademark) manufactured by ASPEX can be used, and the inclusions (compounds) specified in JIS Z 0555:2003 can be measured and analyzed by MQA analysis software (Metals Cleanliness Rating: MQA-MCR (registered trademark)).

[0067] It should be noted that the fine compounds as described above usually also contain oxides that do not contribute to the capture of hydrogen. Therefore, it is preferred to measure only precipitates such as carbides and carbonitrides containing Nb and / or Ti. However, it is sometimes difficult for an inclusion automatic analyzer to distinguish between oxides and these precipitates. In addition, oxides are generally considered to be coarse and oxides of a size of less than 2 μm are trace amounts, so they are not specifically distinguished, and the number density of all compounds with a diameter of 0.1 to 2 μm is measured.

[0068] 3. Chemical composition

[0069] In the austenitic stainless steel of the present embodiment, as described above, the hydrogen embrittlement resistance is improved by controlling the presence state of hydrogen. Therefore, as long as the chemical composition is within the range of austenitic stainless steel, no special restrictions are required. However, the effect of the steel plate of the present embodiment is particularly significant in the composition design that reduces high-priced alloying elements. Therefore, the austenitic stainless steel of the present embodiment preferably has the chemical composition shown below. The reasons for limiting each element are as follows. It should be noted that in the following description, "%" about the content refers to "mass %".

[0070] C: 0.080% or less

[0071] C (carbon) is an element effective in stabilizing the austenite phase and has the effect of increasing strength. However, if C is contained in excess, toughness decreases. Therefore, the C content is preferably 0.080% or less. The C content is more preferably 0.070% or less, more preferably 0.065% or less, and more preferably 0.055% or less. On the other hand, in order to obtain the above-mentioned effect, the C content is preferably 0.010% or more, preferably 0.020% or more.

[0072] Si: 1.00% or less

[0073] Si (silicon) is an effective deoxidizing element and improves hydrogen embrittlement resistance. However, if Si is contained in excess, it will promote the formation of intermetallic compounds such as σ phase, and toughness will decrease. Therefore, the Si content is preferably 1.00% or less. The Si content is more preferably 0.90% or less, more preferably 0.80% or less, more preferably 0.70% or less, and more preferably 0.60% or less. On the other hand, in order to obtain the above-mentioned effect, the Si content is preferably 0.10% or more, preferably 0.20% or more, and preferably 0.30% or more.

[0074] Mn: 2.00% or less

[0075] Mn (manganese) is an element effective for stabilizing the austenite phase and for improving hydrogen embrittlement resistance, but if it is contained in excess, the alloy cost increases. Therefore, the Mn content is preferably 2.00% or less. The Mn content is more preferably 1.90% or less, more preferably 1.80% or less, and more preferably 1.70% or less. On the other hand, in order to obtain the above-mentioned effect, the Mn content is preferably 0.50% or more, preferably 0.70% or more, and preferably 0.90% or more.

[0076] P: 0.050% or less

[0077] P (phosphorus) is an impurity element contained in steel and is an element that reduces mechanical properties. Therefore, the P content is preferably 0.050% or less. The P content is more preferably 0.040% or less, and more preferably 0.030% or less. It is preferred to reduce the P content as much as possible, but excessive reduction of P will increase the refining cost. Therefore, the P content is preferably 0.010% or more.

[0078] S: 0.020% or less

[0079] S (sulfur) is an impurity element contained in steel, which reduces mechanical properties. Therefore, the S content is preferably 0.020% or less. The S content is more preferably 0.015% or less, and more preferably 0.010% or less. It is preferred to reduce the S content as much as possible, but excessive reduction of S will increase the refining cost. Therefore, the S content is preferably 0.0002% or more.

[0080] Cr: 17.0~22.0%

[0081] Cr (chromium) is an element necessary to maintain the corrosion resistance of stainless steel. In addition, Cr also has the effect of improving strength. Therefore, the Cr content is preferably 17.0% or more. The Cr content is more preferably 17.5% or more, and further preferably 18.0% or more. However, if Cr is contained excessively, the toughness decreases. Therefore, the Cr content is preferably 22.0% or less, and preferably 20.0% or less. The Cr content is more preferably 19.5% or less.

[0082] Ni: 8.0~13.0%

[0083] Ni (nickel) has the effect of improving hydrogen embrittlement resistance. In addition, it also has the effect of improving strength. Therefore, the Ni content is preferably 8.0% or more. The Ni content is more preferably 8.5% or more, more preferably 9.0% or more, and more preferably 9.5% or more. However, Ni is a high-priced element, so if Ni is contained excessively, the alloy cost increases. Therefore, the Ni content is preferably 13.0% or less, more preferably 12.0% or less, and more preferably 11.0% or less.

[0084] N: 0.250% or less

[0085] N (nitrogen), like Mn and Ni, is an element effective in improving hydrogen embrittlement resistance. However, if N is contained excessively, internal defects such as pores may sometimes be generated during smelting, and starting points for fracture may easily be generated. As a result, impact resistance decreases. Therefore, the N content is preferably 0.250% or less. The N content is more preferably 0.240% or less, more preferably 0.230% or less, more preferably 0.200% or less, and more preferably 0.170% or less. On the other hand, in order to obtain the above-mentioned effect, the N content is preferably 0.010% or more, preferably 0.040% or more, and preferably 0.070% or more.

[0086] In addition to the above elements, one or more selected from Nb and Ti may be contained within the following ranges. That is, the lower limit of these elements is preferably 0%. The reasons for limiting each element are explained below.

[0087] Nb: 0~0.20%

[0088] Nb (niobium) has the effect of forming fine precipitates and enhancing the function of capturing hydrogen. Therefore, it can be contained as needed. However, Nb is a high-priced element, so if Nb is contained excessively, the alloy cost increases. In addition, due to excessive formation of precipitates, toughness decreases. Therefore, the Nb content is preferably less than 0.20%. The Nb content is more preferably less than 0.18%, and further preferably less than 0.15%. On the other hand, in order to obtain the above-mentioned effects, the Nb content is more preferably more than 0.03%.

[0089] Ti: 0~0.20%

[0090] Ti (titanium), like Nb, has the effect of forming fine precipitates and enhancing the function of capturing hydrogen. Therefore, it can be contained as needed. However, Ti is a high-priced element, so if excessive Ti is contained, the alloy cost increases. Therefore, the Ti content is preferably 0.20% or less. The Ti content is more preferably 0.18% or less, and further preferably 0.15% or less. On the other hand, in order to obtain the above-mentioned effect, the Ti content is more preferably 0.01% or more.

[0091] Thus, Ti and Nb form fine precipitates to enhance the function of capturing hydrogen, and therefore the contents of Ti and Nb preferably satisfy the following formula (i).

[0092] 0.01≤Ti+Nb (i)

[0093] The symbols of the elements in the above formula represent the content (mass %) of the elements contained in the steel, and are set to zero when not contained.

[0094] That is, when the total content of Ti and Nb, which is the value on the left side of formula (i), is less than 0.01, the amount of Ti and Nb in the steel is too low, and it is difficult to form a sufficient amount of compounds required to capture hydrogen. As a result, the number density of compounds with a diameter of 0.1 to 2 μm is likely to be less than 1.0 / mm. 2 Therefore, the value of the left side of formula (i) is preferably 0.01 or more, preferably 0.03 or more, preferably 0.05 or more, and preferably 0.10 or more.

[0095] On the other hand, when the value of the left side of formula (i) exceeds 0.40, the compound is excessively formed, and the number density of the compound with a diameter of 0.1 to 2 μm tends to exceed 10.0 / mm.2 As a result, the hydrogen embrittlement resistance tends to decrease. Therefore, the value of the left side of formula (i) is preferably 0.40 or less, preferably 0.35 or less, and preferably 0.30 or less.

[0096] In addition to the above elements, one or more selected from Mo, Cu, Al, Co, V, W, B, Ca, Mg, Zr, Ga, Hf and REM may be further contained within the range shown below. That is, the lower limit of these elements is preferably 0%. The reasons for limiting each element are explained below.

[0097] Mo: 0~1.0%

[0098] Mo (molybdenum) has the effect of improving strength and corrosion resistance. Therefore, it can be contained as needed. However, Mo is a high-priced element, and if Mo is contained excessively, the alloy cost increases. Therefore, the Mo content is preferably 1.0% or less. The Mo content is more preferably 0.7% or less, more preferably 0.5% or less, and more preferably 0.4% or less. On the other hand, in order to obtain the above-mentioned effects, the Mo content is preferably 0.1% or more, preferably 0.2% or more.

[0099] Cu: 0~1.0%

[0100] Cu (copper) has the effect of improving strength and corrosion resistance. Therefore, it can be contained as needed. However, Cu is a high-priced element, and when Cu is contained excessively, the alloy cost increases. In addition, the steel will be over-hardened, thereby reducing mechanical properties such as toughness. Therefore, the Cu content is preferably less than 1.0%. The Cu content is more preferably less than 0.9%, more preferably less than 0.8%, and more preferably less than 0.6%. On the other hand, in order to obtain the above-mentioned effects, the Cu content is preferably more than 0.1%, more preferably more than 0.2%.

[0101] Al: 0~0.30%

[0102] Al (aluminum) is an element with a deoxidizing effect. Therefore, it can be contained as needed. However, when Al is contained excessively, excessive inclusions will be formed and the surface properties will be reduced. In addition, hot workability will also be reduced. Therefore, the Al content is preferably 0.30% or less. The Al content is more preferably 0.25% or less, more preferably 0.20% or less, more preferably 0.15% or less, and more preferably 0.10% or less. On the other hand, in order to obtain the above-mentioned effect, the Al content is preferably 0.01% or more, preferably 0.02% or more.

[0103] Co: 0~0.50%

[0104] Co (cobalt) has the effect of improving strength and corrosion resistance. In addition, by stabilizing the austenite phase, it also has the effect of improving hydrogen embrittlement resistance. Therefore, it can be contained as needed. However, Co is a high-priced element, and if it is contained excessively, the alloy cost increases. In addition, the processability and toughness will also decrease. Therefore, the Co content is preferably less than 0.50%. The Co content is more preferably less than 0.40%, and more preferably less than 0.30%. On the other hand, in order to obtain the above-mentioned effects, the Co content is preferably more than 0.10%.

[0105] V: 0~0.50%

[0106] Vanadium (V) is dissolved in steel or precipitated in the form of carbonitrides, which has the effect of improving strength. Therefore, it can be contained as needed. However, if V is contained excessively, excessive carbonitrides will be formed, thereby reducing the manufacturability during hot rolling. Therefore, the V content is preferably 0.50% or less. The V content is more preferably 0.40% or less, and more preferably 0.30% or less. On the other hand, in order to obtain the above-mentioned effect, the V content is preferably 0.05% or more.

[0107] W: 0~0.50%

[0108] W (tungsten) has the effect of improving strength and corrosion resistance. Therefore, it can be contained as needed. However, if W is contained excessively, the alloy cost increases. Therefore, the W content is preferably 0.50% or less. The W content is more preferably 0.40% or less, and more preferably 0.30% or less. On the other hand, in order to obtain the above-mentioned effects, the W content is preferably 0.05% or more.

[0109] B: 0~0.0050%

[0110] B (boron) has the effect of strengthening grain boundaries and improving strength. Therefore, it can be contained as needed. However, if B is contained excessively, the workability decreases. Therefore, the B content is preferably 0.0050% or less. The B content is more preferably 0.0030% or less, and more preferably 0.0020% or less. On the other hand, in order to obtain the above-mentioned effect, the B content is preferably 0.0002% or more.

[0111] Ca: 0~0.010%

[0112] Ca (calcium) has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundary. Therefore, it can be contained as needed. However, if Ca is contained excessively, segregation is likely to occur and toughness is reduced. Therefore, the Ca content is preferably 0.010% or less. The Ca content is more preferably 0.007% or less, and more preferably 0.005% or less. On the other hand, in order to obtain the above-mentioned effect, the Ca content is preferably 0.0002% or more.

[0113] Mg: 0~0.010%

[0114] Mg (magnesium) has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundaries. Therefore, it can be contained as needed. However, if Mg is contained excessively, a large number of inclusions will be formed, which will easily become the starting point of fracture, and as a result, the toughness may decrease. Therefore, the Mg content is preferably 0.010% or less. The Mg content is more preferably 0.007% or less, and more preferably 0.005% or less. On the other hand, in order to obtain the above-mentioned effect, the Mg content is preferably 0.0002% or more.

[0115] Zr: 0~0.50%

[0116] Zr (zirconium) has a deoxidizing effect. In addition, it has the effect of improving corrosion resistance. Therefore, it can be contained as needed. However, if Zr is contained excessively, toughness and processability are reduced. Therefore, the Zr content is preferably 0.50% or less. The Zr content is more preferably 0.30% or less, and more preferably 0.20% or less. On the other hand, in order to obtain the above-mentioned effects, the Zr content is preferably 0.01% or more.

[0117] Ga: 0~0.05%

[0118] Ga (gallium) has the effect of improving hot workability. Therefore, it can be contained as needed. However, if Ga is contained excessively, the manufacturability will decrease. Therefore, the Ga content is preferably 0.05% or less. The Ga content is more preferably 0.04% or less, and more preferably 0.02% or less. On the other hand, in order to obtain the above-mentioned effect, the Ga content is preferably 0.001% or more.

[0119] Hf: 0~0.10%

[0120] Hf has the effect of improving strength and hydrogen embrittlement resistance. Therefore, it can be contained as needed. However, if Hf is contained excessively, the workability is reduced. Therefore, the Hf content is preferably 0.10% or less. The Hf content is preferably 0.07% or less, and more preferably 0.05% or less. On the other hand, in order to obtain the above-mentioned effects, the Hf content is preferably 0.01% or more.

[0121] REM: 0~0.10%

[0122] REM has the effect of improving hot workability. In addition, it also has the effect of improving corrosion resistance. Therefore, it can be contained as needed. However, if REM is contained excessively, not only will its effect be saturated, but hot workability will also decrease. Therefore, the REM content is preferably 0.10% or less. The REM content is preferably 0.07% or less, and more preferably 0.05% or less. On the other hand, in order to obtain the above-mentioned effects, the REM content is preferably 0.01% or more.

[0123] REM refers to Sc, Y and 17 other elements in total, including lanthanide elements, and the above REM content refers to the total content of these elements. In industry, REM is often added in the form of mixed rare earth alloys.

[0124] In the chemical composition of the steel plate of the present embodiment, the balance is preferably Fe and impurities. Here, "impurities" refer to components mixed in due to various factors such as raw materials such as ores and scraps and manufacturing processes when austenitic stainless steel is manufactured industrially, and are allowable components within a range that does not adversely affect the steel of the present embodiment.

[0125] 4. Use and shape

[0126] The austenitic stainless steel of this embodiment is preferably used in a high-pressure hydrogen environment or a liquefied hydrogen environment. For example, it is preferably used in parts of a hydrogen manufacturing device or a hydrogen supply device. It should be noted that the parts of the hydrogen manufacturing device or the hydrogen supply device include instruments such as the main body of the tank, the pipe head, the lining, the valve, the heat exchanger, and the distributor.

[0127] It should be noted that the shape of the steel material is not particularly limited. For example, it may be a steel plate. In order to be used for the above-mentioned purpose, in the case of a steel plate, the plate thickness is expected to be 0.25 to 6.0 mm.

[0128] 5. Manufacturing method

[0129] The austenitic stainless steel of the present invention can be stably produced by, for example, the following production method. In the following description, the case of a steel plate is mainly described as an example.

[0130] 5-1. Hot working process

[0131] Stainless steel is melted to produce steel sheets such as slabs. It should be noted that at this time, the chemical composition of the steel sheet is preferably set to the above chemical composition. Then, the steel sheet is heated to a specified temperature to perform hot working to obtain a hot-worked material. In the case of manufacturing steel plates, hot rolling can be performed. The heating temperature during hot working is preferably in the range of 1150 to 1250°C. In addition, in order to make the number density of the compound 1.0 to 10.0 pieces / mm 2 , the working rate in the temperature range of 900-1050°C during hot working is set to 75-90%. For example, in the case of steel plates, the reduction rate in the temperature range of 900-1050°C during hot rolling is 75-90%. When the reduction rate in the above temperature range is less than 75%, the number density of the compound may be less than 1.0 / mm 2 It should be noted that due to manufacturing limitations, the reduction ratio in the above temperature range is preferably 90% or less.

[0132] After hot working, annealing can be performed to adjust the structure as needed. There is no particular restriction on the annealing conditions, but for example, the annealing temperature is preferably in the range of 950 to 1150°C. In addition, the annealing time is preferably in the range of 0.5 to 15 minutes. It should be noted that the annealing atmosphere can be set to an air atmosphere. When annealing is performed after hot working or hot rolling, pickling is performed after annealing to remove the oxide scale. There is no particular restriction on the pickling conditions. Just follow the conventional method.

[0133] 5-2. Cold working

[0134] The hot-worked material, which has been pickled as needed, is cold-worked to obtain a cold-worked material. When manufacturing a steel plate, cold rolling may be performed. There are no particular restrictions on the conditions during cold working, such as the processing rate during cold working, but in the case of a steel plate, the reduction rate is preferably 40% or more in view of its use.

[0135] It should be noted that cold working may be performed multiple times. In addition, heat treatment may be performed between cold working. The conditions for heat treatment are not particularly limited, but for example, it is preferably performed at a temperature range of 950 to 1150° C. for 10 seconds to 10 minutes.

[0136] 5-3. Annealing of cold worked materials

[0137] After the above-mentioned cold working, the cold-worked material is annealed. The annealing temperature is preferably in the range of 950 to 1150°C. In addition, the annealing time is preferably in the range of 5 seconds to 3 minutes. By setting the annealing temperature and annealing time to the above-mentioned range, recrystallization can be promoted and a uniform structure can be obtained. It should be noted that the annealing atmosphere is not particularly limited, for example, it can be set to an LNG combustion atmosphere or a hydrogen-containing reducing atmosphere. That is, LNG annealing or BA annealing is possible. It should be noted that BA annealing tends to cause the amount of released hydrogen [H] to increase. As a hydrogen-containing atmosphere, it is generally a 100% hydrogen atmosphere or an ammonia decomposition gas (75% hydrogen + 25% nitrogen). After the above-mentioned annealing, pickling can be performed as needed. It should be noted that the pickling conditions at this time are not particularly limited. Just follow the conventional method.

[0138] 5-4. Heating treatment

[0139] Next, the cold-worked material that has been annealed and pickled as needed is subjected to a heating treatment. The heating treatment refers to a heat treatment that is maintained at a temperature range of 50 to 400°C for 0.5 to 360 hours. In this way, by performing a heat treatment at a low temperature for a long time, the existence state of hydrogen can be controlled so that the amount of hydrogen released [H], the peak temperature of hydrogen release [Tp], and the peak rate of hydrogen release [Rmax] are within the above range. It should be noted that after the heating treatment, cooling is appropriately performed and each process is adjusted to obtain the desired austenitic stainless steel.

[0140] It should be noted that the atmosphere during the heating treatment is not particularly limited and may be an air atmosphere or an atmosphere of N2 gas or Ar gas at atmospheric pressure.

[0141] Hereinafter, embodiments of the austenitic stainless steel of the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0142] Example

[0143] Stainless steel having the chemical composition shown in Table 1 is melted to obtain a steel sheet. The obtained steel sheet is heated to 1230°C, and the reduction rate in the temperature range of 900-1050°C is set to the conditions shown in Table 2, and hot rolling is performed to obtain a hot-rolled plate with a thickness of 5.0 mm. In some examples, after hot rolling, the hot-rolled plate is annealed by holding at 1100°C for 3 minutes. After hot rolling or annealing of the hot-rolled plate, pickling is performed. Then, the hot-rolled plate is cold-rolled to obtain a cold-rolled plate with a thickness of 1.2 mm. Here, as shown in Table 2, the number of cold rolling is set to 1 or 2 times. Next, the cold-rolled plate is annealed at 1080°C and pickled. After pickling, heat treatment is performed as shown in Table 2. It should be noted that the obtained steel plates are all austenitic stainless steels.

[0144] In Table 2, when the number of cold rolling times is 1, it means that a cold rolling with a cold rolling rate of 76% is performed once to prepare a cold-rolled plate with a thickness of 1.2 mm. In Table 2, when the number of cold rolling times is 2, it means that a cold rolling with a cold rolling rate of 40% is performed once to prepare a steel plate with a thickness of 3.0 mm, and then a heat treatment is performed at 1080°C for 1 minute, and a cold rolling with a cold rolling rate of 60% is performed again to prepare a cold-rolled plate with a thickness of 1.2 mm. In addition, in Table 2, the "LNG" of the cold-rolled plate annealing item means that annealing is performed for less than 1 minute in an LNG combustion atmosphere, and "BA" means that annealing is performed for less than 1 minute in a 0.1MPa H2 atmosphere.

[0145] In Table 2, "1" in the heating treatment item indicates heating treatment at 80°C for 7 days in air atmosphere, and "2" indicates heating treatment at 300°C for 4 hours in N2 gas or Ar gas atmosphere at atmospheric pressure.

[0146] [Table 1]

[0147]

[0148] The obtained steel sheet was subjected to a temperature rise dehydrogenation analysis method from 25°C to 800°C at a temperature rise rate of 100°C / h to investigate the presence of hydrogen (released hydrogen amount [H], peak temperature of hydrogen release [Tp], peak rate of hydrogen release [Rmax]). In addition, the number density of compounds with a diameter of 0.1 to 2 μm was also measured. In addition, the measurement of each value was performed according to the following steps.

[0149] (Existence state of hydrogen)

[0150] After cutting a 10 mm (width direction) × 30 mm (rolling direction) test piece from the steel plate, degrease and clean the test piece with an organic solvent. Next, use the test piece to measure the desorbed hydrogen by temperature dehydrogenation analysis (TDA). In TDA, in an argon atmosphere, the temperature is heated at a rate of 100°C / h in a temperature range of 25°C (room temperature) to 800°C, and the hydrogen released (desorbed) from the test piece is measured by a chromatograph. A TDA curve is prepared based on the measurement results of TDA, and the amount of released hydrogen [H], the peak temperature of hydrogen release [Tp], and the peak rate of hydrogen release [Rmax] are calculated.

[0151] (Number density of compound)

[0152] Prepare the test sample according to JIS Z 0555:2003. Prepare a test area of ​​72mm 2 The sample was tested and the compound with a diameter of 0.1 to 2 μm was confirmed using an inclusion automatic analyzer, and its number density was measured. It should be noted that the inclusion automatic analyzer used MQA (registered trademark) manufactured by ASPEX, and the inclusions (compounds) specified in JISZ 0555:2003 were measured and analyzed using analysis software (MQA-MCR (registered trademark)).

[0153] The hydrogen embrittlement resistance was evaluated in the same manner as the above-mentioned physical property values. A slow strain rate tensile test (also called "SSRT test") was performed to evaluate the hydrogen embrittlement resistance. The SSRT test was performed according to the following steps. First, a tensile test piece with a parallel portion of 4 mm width and 20 mm length was collected. Next, the tensile test piece was used to test the hydrogen embrittlement resistance at a strain rate of 3 × 10 -5 / s, and a tensile test was performed. As a comparative test, a tensile test at the same strain rate was performed at -40°C and 0.1 MPa nitrogen at atmospheric pressure. It should be noted that in some examples, the same tensile test was also performed at -70°C.

[0154] Compared with the results of the comparative test, the case where the tensile strength and the elongation at break did not decrease was regarded as good hydrogen embrittlement resistance, and was recorded as "GOOD" in the table. On the other hand, compared with the results of the comparative test, the case where at least one of the tensile strength and the elongation at break decreased was regarded as poor hydrogen embrittlement resistance, and was recorded as "NG" in the table.

[0155] This evaluation was performed at -40°C and -70°C, and when the tensile strength and elongation at break did not decrease at both temperatures, it was recorded as A in the judgment of hydrogen embrittlement resistance. When the tensile strength and elongation at break did not decrease at -40°C, but the tensile strength and elongation at break decreased at -70°C, it was recorded as B in the judgment of hydrogen embrittlement resistance. When at least one of the tensile strength and elongation at break decreased at -40°C, it was recorded as C in the judgment of hydrogen embrittlement resistance. The results are summarized in Table 2 below.

[0156] [Table 2]

[0157]

[0158] Nos. 1, 2, 4, 5, 7, 9, 11, 13, 15, 17, 18, and 20 satisfying the conditions of the present embodiment have good hydrogen embrittlement resistance, whereas Nos. 3, 6, 8, 10, 12, 14, 16, 19, and 21 to 25 not satisfying the conditions of the present embodiment have poor hydrogen embrittlement resistance.

Claims

1. An austenitic stainless steel, wherein: When the amount of hydrogen released in the temperature range of 25 to 800°C is measured at a temperature increase rate of 100°C / h using the temperature rise dehydrogenation analysis method, The amount of hydrogen released [H] is less than 10.0ppm, The peak temperature [Tp] of hydrogen release is above 350°C. The peak rate [Rmax] of hydrogen release is 0.050 ppm / min or less. The number density of the compound with a diameter of 0.1 to 2 μm in the austenitic stainless steel is 1.0 to 10.0 per mm 2 .

2. The austenitic stainless steel according to claim 1, wherein: The chemical composition of the austenitic stainless steel is, by mass%, C: 0.080% or less, Si: 1.00% or less, Mn: 2.00% or less, P: 0.050% or less, S: 0.020% or less, Cr:17.0~22.0%、 Ni: 8.0-13.0%, N: 0.250% or less, Nb: 0-0.20%, Ti: 0~0.20%, Mo: 0-1.0%, Cu: 0-1.0%, Al:0~0.30%、 Co: 0-0.50%, V:0~0.50%、 W:0~0.50%、 B:0~0.0050%、 Ca: 0~0.010% Mg: 0~0.010%, Zr:0~0.50%、 Ga: 0~0.05%, Hf: 0~0.10%, REM: 0~0.10%, Balance: Fe and impurities.

3. The austenitic stainless steel according to claim 1 or 2, which is used in a high-pressure hydrogen environment or a liquefied hydrogen environment. 4 . The austenitic stainless steel according to claim 1 , which is used for parts of a hydrogen production device or a hydrogen supply device.

Citation Information

Patent Citations

  • Austenitic stainless steel excellent in hot workability and hydrogen embrittlement resistance and production method therefor

    JP2015196842A